OUTSMART HF: A Randomized Controlled Trial of Routine Versus Selective Cardiac Magnetic Resonance for Patients With Nonischemic Heart Failure (IMAGE-HF 1B). Issue 10 (10th March 2020) - Paterson, D. Ian; Wells, George; Erthal, Fernanda; Mielniczuk, Lisa; O'Meara, Eileen; White, James; Connelly, Kim A.; Knuuti, Juhani; Radja, Miroslaw; Laine, Mika; Chow, Benjamin J.W.; Kandolin, Riina; et al.
Abstract : Background: Cardiac magnetic resonance (CMR) is a recommended imaging test for patients with heart failure (HF); however, there is a lack of evidence showing incremental benefit over transthoracic echocardiography. Our primary hypothesis was that routine use of CMR will yield more specific diagnoses in nonischemic HF. Our secondary hypothesis was that routine use of CMR will improve patient outcomes. Methods: Patients with nonischemic HF were randomized to routine versus selective CMR. Patients in the routine strategy underwent echocardiography and CMR, whereas those assigned to selective use underwent echocardiography with or without CMR according to the clinical presentation. HF causes was classified from the imaging data as well as by the treating physician at 3 months (primary outcome). Clinical events were collected for 12 months. Results: A total of 500 patients (344 male) with mean age 59±13 years were randomized. The routine and selective CMR strategies had similar rates of specific HF causes at 3 months clinical follow-up (44% versus 50%, respectively; P =0.22). At image interpretation, rates of specific HF causes were also not different between routine and selective CMR (34% versus 30%, respectively; P =0.34). However, 24% of patients in the selective group underwent a nonprotocol CMR. Patients with specific HF causes had more clinical events than those with nonspecific caused on the basis of imaging classification (19% versus 12%, respectively; P =0.02), but not on clinical assessment (15% versus 14%, respectively; P =0.49). Conclusions: In patients with nonischemic HF, routine CMR does not yield more specific HF causes on clinical assessment. Patients with specific HF causes from imaging had worse outcomes, whereas HF causes defined clinically did not. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01281384. Abstract : Supplemental Digital Content is available in the text.